Bibliometric evaluation of 2011–2021 publications on hydrogen sulfide in heart preservation research - Chen, Mingcong; Zhou, Qian; Wu, Fei; Sun, Fang; Meng, Yang; Zhang, Yang; Zhao, Mingyi (Frontiers in Cardiovascular Medicine, 2023)
Background Hydrogen sulfide (H2S) is known for its unpleasant odor and severe toxicity. However, an in-depth study of H2S showed that it can be used as an important messenger, which can play important physiological and pathological roles in vitro and in vivo. In recent years, the application of H2S in the field of cardiac preservation has attracted the interest and attention of scholars worldwide. H2S plays an effective and protective role in cardiac ischemia/reperfusion injury through antioxidant, anti-inflammatory, and antiapoptotic mechanisms. Objective The purpose of this study is to analyze the current scientific achievements on the application of H2S in the field of cardiac preservation and to provide new ideas for further research. Methods TS = (“hydrogen sulfide” OR “hydrogen sulfide”) AND TS = (“cardiac” OR “heart” OR “myocardium” OR “hearts”) AND TS = (“reperfusion” or “transplantation” or “implanted” or “transplant” or “implantation” or “migration” or “preservation” or “grafting” OR “ischemia” OR “perfusion” or “conservation” or “preserve” or “reservation”) AND DT = (Article OR Review) AND LA = (English) were used as search strategies for data collection from the Science Citation Index-Expanded database of the Web of Science Core Collection. CiteSpace 5.8. R3 and Microsoft Office Excel 2019 were used for data analysis. Results A total of 429 related articles were included, and the total number of articles showed a fluctuating upward trend. We used CiteSpace 5.8. R3 and Microsoft Excel 2019 to evaluate and visualize the results, analyzing institutions, countries, journals, authors, co-cited references, and keywords. Conclusions As increasing evidence shows that H2S plays an indispensable role in the field of cardiac preservation, its mechanistic research and clinical application may become the main focus of future research.